Penggunaan Ekstrak Daun Sirsak, Daun Babadotan, Serai, Daun Pepaya, dan Buah Mengkudu Sebagai Insektisida Nabati Dalam Pengendalian Plutella Xylostella (Lepidoptera : Plutellidae) pada Tanaman Sawi - Arya Abi Sanjaya; Alexander Yaku; Linda Ernawati Lindongi (Fakultas Pertanian Universitas Papua, 2017)
The objective of this research was to identify the effectiveness of some plant extract as organic insecticide and the most effective extract to control P. xylostella in Brassica juncea. This study used completely randomized design with 6 types of organic insecticide as the treatment, i.e control (P0), Annona Muricata leaf extract (P1), Ageratum Conyzoides leaf extract (P2), Cymbopogon citratus leaf extract (P3), Carica papaya leaf extract (P4), and Morinda citrifolia fruit extract (P5). The results showed that all plant extracts were significantly controlled P. xylostella with the efficacy percentage more than 50% within 24 hours after the application. M. citrifolia fruit extract was found to be the most effective organic insecticide among all plant extracts.